The Paradigm of the Goals of Islamic Education from the Perspective of the Qur'an and Hadith Against the Challenges of Modern Education - Thoyibah Thoyibah; Moh. Muslih; Arif Chasanul Muna; Slamet Untung (FKIP - Universitas Riau, 2026)
Modern education is confronted by fundamental problems, including moral crisis, weakening spirituality, educational secularization, dehumanization, and the ethical challenges produced by digital technology. This study aims to examine the paradigm of the goals of Islamic education from the perspective of the Qur'an and Hadith and to analyze its relevance for contemporary education. The study employed a qualitative approach using library research, thematic interpretation (tafsir maudhu'i), and content analysis. Primary sources were purposively selected from Qur'anic verses and Hadith related to tawhid, caliphate, knowledge, morality, and ulul albab, while secondary sources consisted of tafsir works, Islamic education books, and relevant scholarly articles. The findings show that the goals of Islamic education are directed toward forming human beings who are grounded in tawhid, possess noble character, develop knowledge responsibly, uphold religious humanism, and integrate dhikr with critical reasoning through the ulul albab paradigm. These findings indicate that the integration of tawhid, religious humanism, and knowledge offers a practical foundation for strengthening curriculum design, character education, digital ethics, and the responsible use of science and technology. This study concludes that the paradigm of Islamic education can contribute to the development of a contemporary Islamic education system that is adaptive, humanistic, spiritually grounded, and responsive to secularization, moral crisis, and digital disruption.